Squamous intraepithelial lesion associated with atypical squamous cells of undetermined significance in cervical smears - Gilewicz, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2000)
A group of 176 women, which were confirmed to have had atypical squamous cells in the cervical smears, was analysed. Repeated cervical smear and colposcopic examination were conducted; the result of the latter one was the ground to taking the exact biopsy. Cervical examination of 60 women (34,1%.) did not confirm the earlier diagnosis, that is the presence of ASCUS, the examinations of the remaining 116 patients (65,9%) proved the presence of LSIL in 27 cases. 6 patients had HPV cytopathic effect and 1 had HSIL. The examination of the remaining 23 women revealed atypical cells of squamous metaplastic type in smears. Histopathologic examination confirmed the SIL-type changes in 23 cases, HSIL in one case; the results of the SIL examination of 7 women were negative. Co-existance of SIL and the presence of ASCUS featured in the group of women that were confirmed to have 3 or more CIN evolution risk factors or women whose results of recently conducted cervical examinations were beyond normal limits.